'The learning never ends': Exploring teachers' views on the transition from General English to EAP. Issue 23 (September 2016) - Campion, Gemma C.
Abstract: English for Academic Purposes (EAP) in the UK continues to assert its distinctness from 'General English', whilst at the same time actively recruiting its new teachers from a 'General English' background. Despite this, very little has been written about how English teachers should be trained or supported when making the transition to EAP. This paper comprises a critical review of the available literature, highlighting some of its problems and limitations, before progressing to describe a piece of research which attempted to address some of those shortcomings by exploring a number of teachers' views of the challenges faced when beginning to teach EAP, their thoughts on how these challenges can be overcome, and their views on whether EAP teacher qualifications might assist in the process. Through semi-structured interviews with six EAP teachers in the UK, a picture emerges of the transition to EAP as a long-term process, which teachers see as concerning the development of their knowledge (as opposed to their skills) and which can be assisted both by qualifications, and a range of informal development activities. TEAP qualifications are deemed valuable if combined with experience, but are not felt to be useful as a pre-service training measure. Highlights: I explore the transfer from General English to EAP. Learning to teach EAP is a long-term process. The greatest challenge concerns developing the requisite specialised knowledge. Teacher qualifications are most effective when combined with practical experience.